2012
DOI: 10.1590/s0034-89102012005000063
|View full text |Cite
|
Sign up to set email alerts
|

HÓRUS: inovação tecnológica na assistência farmacêutica no sistema único de saúde

Abstract: RESUMOOBJETIVO: Analisar resultados do Sistema Hórus, comparando elementos desse Sistema com algumas experiências internacionais. MÉTODOS:Hórus é uma inovação tecnológica introduzida em 2009 no sistema de informações para a Assistência Farmacêutica do Sistema Único de Saúde. Em 2011, gestores locais e profi ssionais de saúde de 1.247 municípios (16 estados) que aderiram ao Hórus responderam a questionários sobre a assistência farmacêutica na atenção básica e sobre o Sistema Hórus. Estudo descritivo e explorató… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
29

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 11 publications
0
12
0
29
Order By: Relevance
“…The difficulty in this access seems to have been reduced with the adoption of RFM, since 81.3% of the municipalities' pharmacies with RFM had internet access, compared to only 54.1% of municipalities without RFM. In a national study focusing on public pharmacies that use the Horus System, it was found that 49.8% of them had access to the internet 29 . The RFM encourages clinical and pharmacovigilance activities, through adequate infrastructure, bibliographical material and training for pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in this access seems to have been reduced with the adoption of RFM, since 81.3% of the municipalities' pharmacies with RFM had internet access, compared to only 54.1% of municipalities without RFM. In a national study focusing on public pharmacies that use the Horus System, it was found that 49.8% of them had access to the internet 29 . The RFM encourages clinical and pharmacovigilance activities, through adequate infrastructure, bibliographical material and training for pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…This is a descriptive, retrospective cross-sectional study with data from the National Database of Pharmaceutical Services Actions and Services in the SUS (BNDAF) 15 , consisting of a set of data referring to the Basic Component of Pharmaceutical Services registered in Hórus -National Pharmaceutical Services Management System 16 or sent through a web service by the Brazilian municipalities.…”
Section: Methodsmentioning
confidence: 99%
“…Evidenciou-se tal situação nos artigos que abordaram o Sistema Nacional de Gestão da Assistência Farmacêutica (HÓRUS) e o Prontuário Eletrônico do Paciente (PEP), em que os resultados de sua aplicabilidade foram analisados, constatando-se que apesar das dificuldades existentes, a utilização dos mesmos ainda é válida por contribuir na melhoria das condições de saúde (2,(21)(22) . Percebe-se ao longo da análise dos artigos selecionados que os sistemas de informação utilizados pelo SUS são instrumentos importantes e necessários para a obtenção de dados, construção da informação e utilização da mesma para o desenvolvimento de ações direcionadas ao controle, acompanhamento e avaliação da saúde no território nacional.…”
Section: Os Dados Obtidos Pelo Sih-sus Nemunclassified
“…Considerando que inúmeros fatores podem interferir no processo saúde-doença do indivíduo e que a demanda dos usuários tem aumentado, há a necessidade do uso de indicadores de assistência à saúde, com a finalidade de aferir o desempenho do sistema de serviços de saúde para nortear a gestão das políticas públicas e a tomada de decisões. Nessa perspectiva, a introdução das tecnologias de informação em saúde torna-se de fundamental importância (2) . É necessário compreender que um sistema de informações envolve um conjunto de processos que se destina a capturar, processar, transformar, armazenar, manter e produzir informações (3) .…”
Section: Introductionunclassified